New Fault Tolerant Control strategies for nonlinear Takagi-Sugeno systems - Ichalal, Dalil; Marx, Benoît; Ragot, José; Maquin, Didier (Zielona Góra: Uniwersytet Zielonogórski)
New methodologies for Fault Tolerant Control (FTC) are proposed in order to compensate actuator faults in nonlinear systems. These approaches are based on the representation of the nonlinear system by a Takagi-Sugeno model. Two control laws are proposed requiring simultaneous estimation of the system states and of the occurring actuator faults. The first approach concerns the stabilization problem in the presence of actuator faults. In the second, the system state is forced to track a reference trajectory even in faulty situation.
Keywords: Takagi-Sugeno model; fault tolerant control; simultaneous fault and state estimations; Polya?s theorem; Lyapunov theory; input-to-state stability